Synthesis and Characterization of a Gd-DOTA--Permeation Peptide for Magnetic Resonance Relaxation Enhancement of Intracellular Targets - Andrew M. Prantner; Vijay Sharma; Joel R. Garbow; David Piwnica-Worms (Molecular Imaging)
Many MR contrast agents have been developed and proven effective for extracellular nontargeted applications, but exploitation of intracellular MR contrast agents has been elusive due to the permeability barrier of the plasma membrane. Peptide transduction domains can circumvent this permeability barrier and deliver cargo molecules to the cell interior. Based upon enhanced cellular uptake of permeation peptides with D -amino acid residues, an all-D Tat basic domain peptide was conjugated to DOTA and chelated to gadolinium. Gd-DOTA- D -Tat peptide in serum at room temperature showed a relaxivity of 7.94 ± 0.11 mM −1 sec −1 at 4.7 T. The peptide complex displayed no significant binding to serum proteins, was efficiently internalized by human Jurkat leukemia cells resulting in intracellular T1 relaxation enhancement, and in preliminary T1-weighted MRI experiments, significantly enhanced liver, kidney, and mesenteric signals.